Active noise and vibration control (ANVC): current trends, permanent aims and future possibilities - JESSEL, Maurice (Archives of Acoustics, 1985)
The main purpose of this report is to provide a deaper and more adequate understanding of ANVC. A, literature of about 500 papers is now available and has been analysed: ANVC is now developed in many directions; many experiments have been done, proving that several kinds of noise and vibration can be attenuated substantially by active devices. Industrial and commercial exploitation seems a matter for tomorrow. An epistemological obstacle is emphasized, which may be called "anticausality" or teleonomy. A shift of paradigm (in KHUN’s sense) seems to be useful or even necessary to get a fair understanding of how to solve a practical active control problem.